First Experimental Evidence for the Transmission of Chlamydia psittaci in Poultry through Eggshell Penetration. Issue 1 (16th April 2015) - Ahmed, B.; De Boeck, C.; Dumont, A.; Cox, E.; De Reu, K.; Vanrompay, D.
Summary: Eggshell penetration by pathogens is considered a potential route for their transmission in poultry flocks. Additionally, in case of zoonotic pathogens, contact with infected eggs or their consumption can result in human infection. Chlamydia psittaci is a zoonotic bacterium that causes a respiratory disease in poultry and humans. In this study, we provide an experimental evidence for eggshell penetration by C. psittaci . Additionally, we show that after eggshell penetration, C. psittaci could eventually infect the growing embryo. Our findings portend the potential of horizontal trans‐shell transmission as a possible route for the spread of C. psittaci infection in poultry flocks. Considering that horizontal transmission of pathogens via eggs mainly occurs in hatcheries and hatching cabinets, we suggest the latter as critical control points in the transmission of C. psittaci to hatching chicks and broilers, as well as to the hatchery workers and consumers of table eggs.